2021
DOI: 10.1186/s42252-020-00013-x
|View full text |Cite
|
Sign up to set email alerts
|

Capacitance measurements on integrated conductors for detection of matrix cracks in GFRP

Abstract: For the reliable and cost-efficient application of glass fibre polymer composites in structural applications, knowledge of the damage state of the material during operation is necessary. Within this work, a structural health monitoring method based on in-situ electrical capacitance measurements is presented, which enables damage monitoring in glass fibre reinforced polymers. For this purpose, individual glass fibre rovings in a non-crimp fabric were replaced by carbon fibre rovings at regular intervals. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The relative capacitance change curve exhibited a deviation from linear increase at a turning point for both Glass-A-1 and Glass-A-2 specimens. This turning point may indicate the onset of inter-fiber damage, where the relative capacitance change decreases or remains constant while the axial stress increases [ 27 ]. The average relative capacitance change, strain, and axial stress at the turning point were approximately 1%, 1.18%, and 208 MPa, respectively, as summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative capacitance change curve exhibited a deviation from linear increase at a turning point for both Glass-A-1 and Glass-A-2 specimens. This turning point may indicate the onset of inter-fiber damage, where the relative capacitance change decreases or remains constant while the axial stress increases [ 27 ]. The average relative capacitance change, strain, and axial stress at the turning point were approximately 1%, 1.18%, and 208 MPa, respectively, as summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Their research revealed that the structural capacitor deteriorated during the early stages of axial loading, coinciding with the initiation of interfacial cracking between the dielectric layers and CFRP. Recently, Buggisch et al [ 27 , 28 ] developed an analytical model that establishes a correlation between interfacial damage and a reduction in the embedded capacitance value. They embedded interleaved capacitors into GFRP (glass fiber-reinforced polymer), employing three types of electrodes, including carbon fiber yarn, narrow copper wires, and solid copper wires.…”
Section: Introductionmentioning
confidence: 99%
“…However, this system is also very important for many other applications, for instance, in the world of sensors. As a matter of fact, a charged annulus is a key component for building coplanar capacitive sensors which are used for a non-destructive evaluation of materials [24][25][26][27]. The most common design of a coplanar capacitive sensor has two coplanar electrodes, namely, plates with any given shape (square/rectangular, circular, etc).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the capacitance value can be altered by changing the dielectric constant. For example, induced interfacial damages such as cracks in the epoxy matrix may allow the air to enter between layers, which in turn can alter the effective dielectric (flaws /damage detector) [8]. Also, this type of sensor can be used for detecting water intrusion in composite structures (humidity sensor) where the change of dielectric properties of the material is directly affected by the changing moisture content [9].…”
Section: Methodsmentioning
confidence: 99%